EFFECTIVITY OF PNEUMATIC RETINOPEXY PROCEDURE IN PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT (RRD) - Soedarman, Soefiandi; Sjamsoe, Soedarman; Girsang, Waldensius; Elvioza, Elvioza; Agustiawan, Referano; Adriono, Gitalisa Andayani (International Journal of Retina, 2020)
Introduction  : To evaluate the effectiveness of pneumatic retinopexy (PR) for repair of primary rhegmatogenous retinal detachment (RRD) with respect to single operation success (SOS) and best corrected visual acuity (BCVA). Method : This retrospective review comprised 8 eyes with primary rhegmatogenous retinal detachment with superior break that undergone pneumatic retinopexy as the initial procedure between 2009-2014 at Jakarta Eye Center, Indonesia. Result : The mean age of subjects was 49 Â± 14.35 years. Four subjects (50%) had Single operation had only done success after 6 months of observation. The eyes that failed single procedure underwent vitrectomy and silicon oil tamponade.  Subjects that only done single procedure had better BCVA (0.01 Â± 1,3 logMAR) compare to subjects that done secondary procedure (0.3 Â± 0.42 logMAR) after 6 months of observation. Conclusion : Pneumatic retinopexy is still an effective procedure for primary rhegmatogenous retinal detachment with superior breaks although in our study the single operation success was 50%.